(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The main objective of this article is to introduce the idea of q-rung orthopair (m, n)-fuzzy subgroups of a finite group. We discuss the concept of q-rung orthopair (m, n) – fuzzy subgroups as a combination of intuitionist fuzzy subgroup and Pythagorean fuzzy subgroup. We provide the definition of q-rung orthopair (m, n) – fuzzy subgroup and examine various properties associated with it. Finally we analyze q-rung orthopair (m, n)- fuzzy cosets, (m, n) – fuzzy normal subgroups and (m, n)- fuzzy level subgroups.